ChemInform Abstract: Ruthenium‐Catalyzed Asymmetric Transfer Hydrogenation of 1‐Aryl‐Substituted Dihydroisoquinolines: Access to Valuable Chiral 1‐Aryl‐Tetrahydroisoquinoline Scaffolds. Issue 38 (30th August 2013) - Wu, Zi; Perez, Marc; Scalone, Michelangelo; Ayad, Tahar; Ratovelomanana‐Vidal, Virginie
Abstract Notable features of the process include mild conditions, operational simplicity, high yields and enantioselectivities.